Practical guidelines for reporting results in single- and multi-component analytical calibration: A tutorial - Olivieri, Alejandro Cesar (2015)
Practical guidelines for reporting analytical calibration results are provided. General topics, such as the number of reported significant figures and the optimization of analytical procedures, affect all calibration scenarios. In the specific case of single-component or univariate calibration, relevant issues discussed in the present Tutorial include: (1) how linearity can be assessed, (2) how to correctly estimate the limits of detection and quantitation, (2) when and how standard addition should be employed, (3) how to apply recovery studies for evaluating accuracy and precision, and (4) how average prediction errors can be compared for different analytical methodologies. For multi-component calibration procedures based on multivariate data, pertinent subjects here included are the choice of algorithms, the estimation of analytical figures of merit (detection capabilities, sensitivity, selectivity), the use of non-linear models, the consideration of the model regression coefficients for variable selection, and the application of certain mathematical pre-processing procedures such as smoothing.